Synthesis, structural elucidation and DNA binding study of fluorine substituted organotin(IV) dithiocarbamates. (14th December 2015) - Noureen, Shama; Sirajuddin, Muhammad; Ali, Saqib; Shaheen, Farzana; Tahir, Muhammad Nawaz
Graphical abstract: A series of organotin(IV) compounds were synthesized and characterized successfully. The synthesized compounds interact with SS-DNA via the intercalation mode of interaction. Abstract: A series of new tri- and diorganotin(IV) derivatives of an S-donor ligand with the formulae Me3 SnL (1 ), n -Bu3 SnL (2 ), Ph3 SnL (3 ), Me2 SnClL (4 ), Bu2 SnClL (5 ), Ph2 SnClL (6 ) and Me2 SnL2 (7 ) were prepared by the reaction of organotin(IV) chlorides with the ligand L = 4-[bis(4-flourophenyl)methyl]piperazinium 4-[bis(4-flourophenyl)methyl]piperazine-1-carbodithioate, refluxing for 6–7 h, using dry toluene as a solvent. The synthesized compounds were characterized by elemental analysis (CHN), FT-IR, multinuclear NMR ( 1 H and 13 C) and single crystal X-ray crystallography. The NMR study reveals a four coordinated geometry in the solution state for complexes1 –7 . It was also concluded from the crystallographic data that the synthesized complexes exhibit four coordinated monodentate structures in the solid state. A DNA binding study was performed by UV–Visible spectroscopy, viscometric measurements and cyclic voltammetry. These techniques showed an intercalative mode of interaction for the compounds with SS-DNA. A new and efficient strategy to identify pharmacophores and anti-pharmacophores sites in dithiocarbamates derivatives for antibacterial/antifungal activity using Petra, Osiris and Molinspiration (POM) analyses was also carried out. The synthesized complexes have negative values of miLog P which indicate their ability to penetrate through bio-membranes. Parameters like miLog P and TPSA for the studied complexes fall in a range that is to be expected for compounds predicting oral absorption of a drug, which means they have good bioavailability. Based on the four precise criteria (GPCR ligand, ion channel modulator, Kinase inhibitor and nuclear receptor ligand) the synthesized compounds are expected to have drug properties.